Chest Radiograph Severity and Its Association With Outcomes in Subjects With COVID-19 Presenting to the Emergency Department. - Kotok, Daniel; Rivera Robles, Jose; Girard, Christine E.; Shettigar, Shrutti K.; Lavina, Allen P.; Gillenwater, Samantha R.; Kim, Andrew I.; Hadeh, Anas (Respiratory Care, 2022)
BACKGROUND: Severity of radiographic abnormalities on chest radiograph in subjects with COVID-19 has been shown to be associated with worse outcomes, but studies are limited by different scoring systems, sample size, subject age, and study duration. Data regarding the longitudinal evolution of radiographic abnormalities and its association with outcomes are scarce. We sought to evaluate these questions using a well-validated scoring system (the Radiographic Assessment of Lung Edema [RALE] score) using data over 6 months from a large, multihospital health care system. METHODS: We collected clinical and demographic data and quantified ra-diographic edema on chest radiograph obtained in the emergency department (ED) as well as on days 1-2 and 3-5 (in those admitted) in subjects with a nasopharyngeal swab positive for SARS-CoV-2 by polymerase chain reaction (PCR) visiting the ED for coronavirus disease 2019 (COVID)-19-related complaints between March-September 2020. We examined the association of baseline and longitudinal evolution of radiographic edema with severity of hypoxemia and clinical outcomes. RESULTS: Eight hundred and seventy subjects were included (median age 53.6; 50.8% female). Inter-rate agreement for RALE scores was excellent (interclass correlation coefficient 0.84 [95% CI 0.82-0.87], P < .001). RALE scores correlated with hypoxemia as quantified by SpO2/FIO2 (r = -0.42, P < .001). Admitted subjects had higher RALE scores than those discharged (6 [2-11] vs 0 [0-3], P < .001). An increase of RALE score ≥ 4 was associated with worse 30-d survival (P = .006). Larger increases in the RALE score were associated with worse survival. CONCLUSIONS: The RALE score was reproducible and easily implementable in adult subjects presenting to the ED with COVID-19. Its association with physiologic parameters and outcomes at baseline and longitudinally makes it a readily available tool for prognostication and early ICU triage, particularly in patients with worsening radiographic edema.